Metode Pembelajaran Jarak Jauh Tahsin dan Tahfidz Al-Qur’an pada SMA Islam Terpadu Nurul Fikri Boarding School Bogor - Mohammad Alfian Musthofa; Qowaid Qowaid; Efrita Norman (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
The pandemic caused by the COVID-19 outbreak that is currently hitting educational institutions has made various strategies in continuing the learning process, especially in terms of learning the Qur'an. This is as attempted by the Integrated Islamic High School Nurul Fikri Boarding School Bogor to make a remote learning program of the Qur'an using the Tahsin and Tahfidz Al-Qur'an methods. This distance learning Al-Qur'an program was created during the covid-19 outbreak and is still being used today in 2022. This study aims to describe how the distance learning method is tahsin and tahfidz Al-Qur'an, distance learning tahsin and tahfidz of the Qur'an and their positive and negative impacts. The research method used is a qualitative research method. The subjects in this study were 4 people. Data analysis was carried out using Miles Huberman's analysis with the first step being data collection followed by data reduction and data presentation, then ending with verification or conclusions. The results of data analysis show that the Tahsin Method (Tanbiqo Tanbiqu) uses a practical method. The Integrated Islamic High School Nurul Fikri Boarding School Bogor requires prospective students to memorize the Qur'an before continuing on the tahfidz process, they must go through the tahsin process first to avoid two mistakes, namely fatal errors (lahnul jali) and minor errors (lahnul khafi). The method used is a practical method with the basic discussion material makhorijul letters and their application to the Qur'an. The learning method of tahsin and tahfidz Al-Qur'an used at SMA Terpadu Nurul Fikri is a very good method to use in learning tahsin and tahfidz Al-Qur'an. The Tanbiqo Tanbiqu method and Nurul Fikri's tahfidz method look very comprehensive with other Qur'anic tahsin and tahfidz learning methods. Learning materials using Tanbiqo Tanbiqu are given to new students for the first 3 months of admission, as a preparation to start memorizing the Qur'an and Nurul Fikri's tahfidz method using the 1) Jama'i, 2) Juz'i, 3) Talqin, 4) methods Muroja'ah. Keywords: Tahsin, Tahfidz, Al-Qur'an, Distance Learning Method